Understanding the links between agriculture and health - Hawkes, Corinna; Ruel, Marie T. (International Food Policy Research Institute, 2006)
Policymaking initiatives in agriculture and public health are often pursued in a parallel and unconnected fashion. Yet coherent, joint action in agriculture and health could have large potential benefits and substantially reduce risks for the poor. Among development professionals there is growing recognition that agriculture influences health, and health influences agriculture, and that both in turn have profound implications for poverty reduction. This recognition suggests that opportunities exist for agriculture to contribute to better health, and for health to contribute to agricultural productivity. To take advantage of these opportunities, however, it is crucial to understand the precise linkages between the two sectors. How do the linkages work? Where do opportunities for joint action lie, and what are the impediments? How can the agricultural and health sectors work together more closely and thereby contribute to addressing poverty?